New diagnosis for species of Plutomurus Yosii (Collembola, Tomoceridae), with descriptions of two new species from Georgian caves - Barjadze, Shalva; Baquero, Enrique; Soto-Adames, Felipe N.; Giordano, Rosanna; Jordana, Rafael (Zootaxa, 2016)
Two new species of the genus Plutomurus, P. revazi sp. nov. from Prometheus and Satsurblia caves and P. eristoi sp. nov. from Satevzia Cave are described, illustrated and differentiated from other morphologically closely related species. A high variability in the number of teeth in the claw, unguiculus and mucro of P. revazi sp. nov. demonstrate that these characters are not useful for species diagnosis. However, dorsal chaetotaxy was shown to be stable character for this purpose. Analysis of DNA sequences for the COI and 28S genes is congruent with species-level groups delimited by chaetotaxy, and provide additional support for chaetotaxy as the most reliable morphological character system to distinguish species in Plutomurus. A key to species of the genus Plutomurus found in Georgia is provided, which for the first time includes characters of the macrochaetotaxy.